The Town Planning of Hellenistic Sikyon - Lolos, Yannis; Gourley, Ben (Archäologischer Anzeiger, 2014)
This study offers an attempt to reconstruct the town planning of Hellenistic Sikyon based mainly on the results of the recent intensive surface and geophysical surveys. The fortifications of the city were mapped over a total length of ca. 200 m and included seven gates. The city grid was oriented northsouth, eastwest, and included square insulae 60–65 m in length. The streets had an average width of 6 m with the exception of at least one avenue, almost 10 m wide. The estimated surface area of the agora ranges between 37,000 m2 and 59,000 m2, which would have corresponded to an area of 7.5 to 12 insulae. Towards the end of the article we examine various factors that are likely to have played a role in the design and application of the specific grid.